Convention and basic rules of procedure of IICA - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
This volume of IICA’s Official Documents Series contains the text of the Convention on the Inter-American Institute for Cooperation on Agriculture, and the texts of the Rules of Procedure of the Institute’s governing bodies: the InterAmerican Board of Agriculture (IABA), the Executive Committee and the General Directorate. The Rules of Procedure were approved during the First Regular Meeting of the IABA in August 1981. This volume includes the amendments to these Rules, adopted by the IABA and the Executive Committee in subsequent meetings. The date of the meeting during which the amendments were approved appears after each amended Article.